2014
DOI: 10.1007/s10858-014-9859-6
|View full text |Cite
|
Sign up to set email alerts
|

Towards automatic protein backbone assignment using proton-detected 4D solid-state NMR data

Abstract: We introduce an efficient approach for sequential protein backbone assignment based on two complementary proton-detected 4D solid-state NMR experiments that correlate H N i /N i with CA i /CO i or CA i-1 / CO i-1 . The resulting 4D spectra exhibit excellent sensitivity and resolution and are amenable to (semi-)automatic assignment approaches. This strategy allows to obtain sequential connections with high confidence as problems related to peak overlap and multiple assignment possibilities are avoided. Non-unif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 43 publications
0
42
0
Order By: Relevance
“…The use of nonuniform sampling (NUS) for solid-state NMR is attracting attention [69, 73, 75, 9092]. In solution, NUS is typically applied to speed up the data collection, and this mode has also been explored in the solids NMR experiments.…”
Section: Sample Preparation and Mas Nmr Methods For Structural Anamentioning
confidence: 99%
See 1 more Smart Citation
“…The use of nonuniform sampling (NUS) for solid-state NMR is attracting attention [69, 73, 75, 9092]. In solution, NUS is typically applied to speed up the data collection, and this mode has also been explored in the solids NMR experiments.…”
Section: Sample Preparation and Mas Nmr Methods For Structural Anamentioning
confidence: 99%
“…demonstrated that a set of four-dimensional experiments, (H)CACO(CA)NH and (H)COCA(CO)NH, could be used to collect data with appropriate sensitivity and resolution in a reasonable amount of time using NUS. With 20% nonuniform sampling coverage, the combined experiment time could be reduced from 55 days to 11 days [92]. Another study by Lin and Opella demonstrated that with NUS coverage of 25–33%, two- and three-dimensional datasets could be collected and reconstructed using compressed sensing processing, thus saving experiment time [90].…”
Section: Sample Preparation and Mas Nmr Methods For Structural Anamentioning
confidence: 99%
“…Failure to assign spectra is often the bottleneck to structure determination. Under MAS, sequence-specific resonance assignment is accomplished primarily by interresidue matching with 13 C shifts, either using 13 C detection (Hong 1999;Rienstra et al 2000;Böckmann et al 2003) or more recently, 1 H detection (van Rossum et al 2003;Knight et al 2011;Linser et al 2011;Ward et al 2011;Marchetti et al 2012;Zhou et al 2012; Barbet-Massin et al 2014;Xiang et al 2014).…”
mentioning
confidence: 99%
“…Although only 15 N and 13 C chemical shifts are considered in the simulations described above, multidimensional solid state NMR spectra of proteins that include 1 H chemical shifts are also obtained in some experiments [4648]. Simulations that include 1 H chemical shifts can be carried out with the mcassign2b program, without any modifications, and could be used to design assignment strategies for such experiments.…”
Section: Discussionmentioning
confidence: 99%